Influences of suction pipe structures on hydraulic performance and internal flow of electric coolant pumps - Yang, Anlong; Gu, Yandong; Cheng, Li; Zhao, Wenpeng (Frontiers in Energy Research, 2024)
The Electric Coolant Pump (ECP) serves as a critical component in the thermal management of electric vehicles. To fulfill the requirements of pressurizing and circulating coolant for various components, a complex structure with multiple pipes is integrated into the pump inlet. This study focuses on the design and analysis of three suction pipe structures: a straight pipe (Case A), a bend (Case B), and a combination of a bend with manifolds (Case C). The objective is to explore the impact of suction pipe structure on the hydraulic performance, flow pattern, temperature distribution, and vorticity of the ECP. Taking into account the variability of coolant physical parameters with temperature, the ECP is numerically simulated with the unsteady Reynolds-Averaged Navier-Stokes (RANS) equation and the Shear Stress Transport k-ω turbulence model. The experimental and numerical results exhibit good agreement. Case A demonstrates the highest efficiency, Case B follows as the second most efficient, and Case C displays the lowest efficiency. However, the pressure rise remains essentially consistent for all cases. The average efficiency of Case B and Case C is 1.18% and 2.13% lower than Case A. The temperature of the ECP rises with an increase in coolant temperature. The temperature of the printed circuit board (PCB) surpasses that of the motor. Case A exhibits the most favorable flow pattern, while Case C demonstrates the least favorable. The bend introduces secondary flow, further intensified by the manifold, leading to an increase of vorticity. The high vorticity zones expand as the flow rate increases. This study offers valuable insights for the optimization of the ECP suction pipe structure.